2001
DOI: 10.1046/j.1365-2958.2001.02478.x
|View full text |Cite
|
Sign up to set email alerts
|

The elimination of the yeast [PSI+] prion by guanidine hydrochloride is the result of Hsp104 inactivation

Abstract: SummaryIn the yeast Saccharomyces cerevisiae, Sup35p (eRF3), a subunit of the translation termination complex, can take up a prion-like, self-propagating conformation giving rise to the non-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
221
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(230 citation statements)
references
References 61 publications
7
221
0
2
Order By: Relevance
“…46,47 Given the sensitivity of RAC and Ssb mutants to cations including GuHCl, 48,49 we used a somewhat lower concentration (2.5 mM) than is typically used for prion curing (3-5 mM). Cells were plated on YEPDCGuHCl, incubated until single colonies formed, then individual colonies restreaked onto fresh YEPDCGuHCl plates to obtain single colonies.…”
Section: The Rac Antagonizes Induced and Spontaneous Formation Of Thementioning
confidence: 99%
“…46,47 Given the sensitivity of RAC and Ssb mutants to cations including GuHCl, 48,49 we used a somewhat lower concentration (2.5 mM) than is typically used for prion curing (3-5 mM). Cells were plated on YEPDCGuHCl, incubated until single colonies formed, then individual colonies restreaked onto fresh YEPDCGuHCl plates to obtain single colonies.…”
Section: The Rac Antagonizes Induced and Spontaneous Formation Of Thementioning
confidence: 99%
“…Investigations into the mechanism of action of Hsp104 have been facilitated by experiments showing that Hsp104 in vivo can be inactivated by treating yeast with low levels of guanidinehydrochloride (Gdn) (20)(21)(22). Whereas it was demonstrated many years ago that such treatment cures [PSI ϩ ], recently it was shown that Gdn acts by inhibiting Hsp104 ATPase activity (23,24).…”
Section: Propagation Of the Yeast Prion [Psimentioning
confidence: 99%
“…On the other hand, others have suggested that Hsp104 is required only to break up aggregates to replicate them so that they are passed on to daughter cells when yeast divide (14-16). It was further proposed that Hsp104 breaks up only the small aggregates, whereas large aggregates form dead-end complexes unable to propagate the prion trait (15,(17)(18)(19).Investigations into the mechanism of action of Hsp104 have been facilitated by experiments showing that Hsp104 in vivo can be inactivated by treating yeast with low levels of guanidinehydrochloride (Gdn) (20)(21)(22). Whereas it was demonstrated many years ago that such treatment cures [PSI ϩ ], recently it was shown that Gdn acts by inhibiting Hsp104 ATPase activity (23,24).…”
mentioning
confidence: 99%
“…Although GdmCl seems to inhibit the replication of the prions (15,16), several lines of evidence suggest that it does not target the prion proteins themselves but Hsp104. First, GdmCl blocks the disaggregase activity of Hsp104 in vivo and reduces the thermotolerance of yeast (17,18). Second, both GdmCl-treated and Hsp104-deficient yeast cells have similar phenotypes in respect to prion propagation (17,18).…”
mentioning
confidence: 99%
“…First, GdmCl blocks the disaggregase activity of Hsp104 in vivo and reduces the thermotolerance of yeast (17,18). Second, both GdmCl-treated and Hsp104-deficient yeast cells have similar phenotypes in respect to prion propagation (17,18). A recent report showed that, in yeast strains with a point mutation in Hsp104 (D184S), prion phenotypes can no longer be cured by GdmCl (19).…”
mentioning
confidence: 99%